Migrasi Suku Banjar di Paluh Manan, Sumatera Utara: Dinamika Sosial dan Budaya dalam Perspektif Historis - Zain, Muhammad Fajar Aditya; Ramadhan, Muhammad Faisal; Siregar, Nofi Dayanti; Siregar, Yusra Dewi (Medan Resource Center, 2023)
This study aims to examine the social and cultural dynamics within the Banjar community that migrated to the Paluh Manan region of North Sumatra, and to understand how this migration process has impacted their social structure and culture from a historical perspective. Employing a qualitative approach, the research utilizes data collection methods such as in-depth interviews, observations, and literature review. The findings indicate that the migration of the Banjar people to Paluh Manan has brought significant changes in social, economic, and cultural aspects, including adaptation to the new environment, changes in lifestyle, and interactions with the local community. The study also highlights how the history of migration has shaped the identity and traditions of the Banjar in Paluh Manan, as well as the challenges and opportunities faced in preserving their culture amidst rapid social changes. These findings are expected to contribute to a deeper understanding of ethnic migration and cultural dynamics within the Indonesian context, as well as provide insights for more inclusive and adaptive social policies and planning.